SINERGITAS PENTAHELIX DALAM PEMULIHAN PARIWISATA PASCA BENCANA ERUPSI GUNUNG API SINABUNG DI KABUPATEN KARO, SUMATERA UTARA - Rizkiyah, Putri; Liyushiana, Liyushiana; Herman, Herman (Jurnal IPTA (Industri Perjalanan Wisata); Vol 7 No 2 (2019): Jurnal IPTA (December 2019), 2019)
The eruption of Mount Sinabung had a pretty heavy impact on Karo District, in terms of the tourism economy sector, which has been the signature economy motor of this region. For almost 1 (one) decade, the eruption disaster shook, the recovery effort is still stagnant despite various government efforts. Therefore, this study aims to carry out an inventory of economic recovery, particularly in the tourism sector in Karo District by including the pentahelix synergy model as a surefire strategy to encourage community independence and achieve faster and more sustainable recovery goals. This study uses qualitative research methods with the main data collection techniques through a Focus Group Discussion. The results achieved indicate several strategies can be carried out to restore tourism in Karo District, including: rehabilitation of the image of Karo district as a safe tourist destination, strengthening the disaster awareness movement, infrastructure recovery, to the creation of signature tourism products based on disaster tourism, health tourism and agro tourism. This study also illustrates what roles can be taken by the government, academia, industry, society and the media in each strategy and proposed program.